POTENTIAL OF FUNGAL ENDOPHYTES TO ANTAGONISE PUCCINIA STRIIFORMIS CAUSING WHEAT YELLOW RUST - H. A. Anwaar1; M. Z. Mansha; M. Z. Ahmed; M. Abid; M. Sajid; Z. M. Sarwar; Ummad ud din Umar; M. M. Alam1; R. Perveen; S. Chohan; M. S Shafique (Journal of Animal and Plant Sciences, 2020)
Intense exploitation of pesticides has instigated agricultural and environmental hazards. Microbial inoculation is an alternate to pesticides for antagonising pathogens and is an environmental friendly approach. In this study, we evaluated the potential of fungal endophytes of desert plants, to control the yellow rust of wheat (Triticum aestivum L.) caused by Puccinia striiformis. Four endophytes i.e. Colletotrichum lindemuthianum, Piriformospora indica, Acremonium lolii and Trichoderma viride were selected in vitro, on the basis of their positive impact on the growth of wheat seedlings. Seeds of two rust susceptible wheat genotypes namely Fareed-06 and Shafaq-06 selected by screening experiment against the disease were treated with spore suspensions of these four endophytes separately using randomized complete block design under factorial arrangement. The data concerning area under disease progress curve (AUDPC), final disease severity (FDS), coefficient of infection (CI), thousand grains weight (TGW) and grain yield (GY) was recorded. Results showed that endophytic inoculated susceptible wheat genotypes exhibited the tolerance against the Puccinia striiformis. The endophyte P. indica significantly decreased the final disease severity and area under disease progress curve, resulting an increase in the grain yield 12.2% in the Fareed-06 and Shafaq-06 followed by the endophytes T. viride, C. lindemuthianum and A. lolii as 10.6%, 06.2% and 04.2% respectively. The present study concluded that fungal endophytes are valuable microbes which can be employed to induce tolerance against P. striiformis and yellow rust for better and sustainable wheat production.
Keywords: Piriformospora indica; endophytes; disease severity; grain yield; tolerance